Evaluate the Effectiveness of a Structured Teaching Programme on Dietary Management Among Hypertensive Patients at Selected Tertiary Care Hospital in Mysuru (Journal of Nursing in Global and Community Health, 2026)
Hypertension is one of the most common chronic illnesses affecting adults worldwide and is a major contributor to cardiovascular morbidity and mortality. pharmacological management is important in maintaining blood pressure, lifestyle and dietary practices remain essential for controlling in long- term. Educational interventions can improve awareness and encourage healthy dietary habits practices among individuals with hypertension, Objectives: 1. To assess the pre-test level of knowledge regarding dietary management among hypertensive patients at a tertiary care hospital in Mysuru. 2. To evaluate the effectiveness of the Structured Teaching Programme on dietary management among hypertensive patients by comparing pre-test and post-test knowledge scores. 3. To determine the association between post-test knowledge scores and selected demographic variables of hypertensive patients. Research Methodology: used are, a pre-experimental one-group pre-test and post-test research design was adopted for the study. Sixty hypertensive patients attending the outpatient and inpatient departments of Selected Tertiary care Hospital that is JSS Hospital, Mysuru, were selected using convenience sampling. Knowledge regarding dietary management was assessed with a structured questionnaire before the intervention that is pretest method and again after the structured teaching programme about detailed dietary management of hypertension that is posttest. Results: The findings demonstrated a considerable increase in knowledge scores following the administration of educational intervention that is Structured teaching programme. The mean post-test score (21.6 ± 3.8) was higher than the mean pre-test score (12.4 ± 4.2). Statistical analysis revealed a significant improvement in knowledge (t = 12.45, p < 0.001). Educational status and duration of illness showed a significant association with post-test scores. Conclusion is Structured Teaching Programme by the researcher was effective in improving participants’ understanding of dietary management for hypertension which supports better self-care practices to improved blood pressure management.
Keywords: DASH diet; Dietary management; Hypertension; Lifestyle modification; Nursing intervention; patient teaching